Rehabilitation of Ecologically Polluted Areas in the Absheron Peninsula, use of the Area Under Greenery: Rehabilitation of Ecologically Polluted Areas in the Absheron Peninsula, use of the Area Under Greenery - Aliyev, Z. H. (B.R. Nahata Smriti Sansthan Agricultural Extension Journal (AEXTJ), 2021)
In the article, the development of oil fields in the Absheron Peninsula is sufficient to improve the health of the soil by conducting research on soil that has been intensively man-made as a result of the expansion of oil refining and petrochemical industry. The ecologically polluted area was mapped on the basis of geographic information system (GIS) technology and a methodology for planting new greenery was developed by conducting soil research. The ecologically polluted territory was applied to the map on the basis of GIS technology, soil research was conducted, and a methodology for planting new green plantations was developed.